Scoping Review: Pentahelix Community Empowerment Development Strategy as an Effort to Improve the Quality of Life during the Covid-19 Pandemic in Low Middle Income Countries LMIC - Nurlatif, Rr. Vita; Kushermanto, Andi; Isrofah, I; Priharwanti, Ardiana; Prasetyo, Eko Budi (KnE Social Sciences, 2024)
The Covid-19 pandemic has had a multi-sectoral impact not only on the health sector, but also on multi-sectors, such as health, education, economy, and other crucial and supporting sectors. During the pandemic, that hit more than 200 countries, various community empowerment strategies have emerged, all of which have the same pattern, namely stakeholder engagement. The community empowerment strategy, which aims at improving the quality of life based on family is the way out or the most possible way out to improve public health status during the new normal, especially in middle and lower countries. A systematic approach was taken to search for literature using the PubMed DataBase, Health Evidence, Cochrane, and Science Direct. Then the results of empirical research that met the criteria were carried out using critical analysis based on the PCC (Population, Concept, and Context) approach, using the keywords ((((community) health empowerment) OR (health empowerment)) OR (Community health development)) OR (Stakeholder engagement)) AND (((Community empowerment development strategy)) OR (Community development strategy))) AND (((Improving the quality of live based on Thought families The Age of New Habits)) OR (quality of live)) OR (Improving quality of live family based)))) AND (Low Middle Income Country). The results are based on the results of a scoping review of 9 articles, five models of pentahelix community empowerment strategies were obtained as an effort to improve the quality of life during a pandemic in lower middle-class countries. Suggestions for the involvement of stakeholders and the community are key factors that must always be synergized as a way out of community empowerment during a pandemic. Keywords: stakeholder engagement, quality of life, new habits, low middle-income country